Some aspects of the effect of temperature on the respiratory and cardiac activities of the Cichlid Teleost Tilapia mossambica - Josman, V (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1971)
The importance of the cichlid teleost Tilapia mossambica as a protein source, coupled with its remarkable adaptability, has resulted in its introduction into many water systems throughout the tropical, sub-tropical and even temperate regions of the world. However, its successful exploitation of these waters is dependent very largely upon the value of minimum temperatures and their duration. For e.g. Long et al (1961) has drawn attention to the tremendous mortalities of T. mossambica that occur in shallow water bodies during the precipitous temperature decreases that accompany the winter monsoons in Vietnam and other eastern countries, even at temperatures as high as 14 or 16º C. Coehe (1967) does not recommend stocking with T. mossambica where temperatures are not above 14º C all the time. Ailanson et al (1962) conclude, after an experimental study, that low temperatures (13º C or lower) in South African highveld dams in winter are certainly an important factor in the extensive mortalities of T. mossambica that have been reported from these dams. Jubb (1961) also reports that this species is often killed during a severe winter in Rhodesia. Intro., p.1.
Keywords: Fishes -- Effect of temperature on; Cichlids